A mobile app for stooping - Ng, Yew Jie (Nanyang Technological University, 2024)
Stooping, a rising trend in North America, involves giving away unwanted or unneeded items to others. This project aims to create a mobile application utilised around this concept. The main goal is to develop an application with basic features such as item listing, editing of item details, profile management, and end to end users communication. This project makes use of Firebase services for data retrieval, storage, and user authentication. Moreover, messaging, item editing features and media posting are designed to improve user experience and building a community around it. Flutter and Dart programming languages are used for the app development while using Firebase services for backend. Future research could explore additional features and faster runtime in further improving the application's functionality and usability. To conclude, this application provides a way to foster community and help those who are in needs, and at the same time, to promote recycle of goods, resulting in benefitting the environment.